Sustainable Laboratory Capacity Building After the 2014 Ebola Outbreak in the Republic of Guinea - Ndjomou, Jean; Shearrer, Scott; Karlstrand, Brendan; Asbun, Carmen; Coble, Jesse; Alam, Jane S.; Mar, Mar P.; Presser, Lance; Poynter, Scott; Michelotti, Julia M.; Wauquier, Nadia; Ross, Casey; et al. (Frontiers in Public Health, 2021)
Background: The 2014–2016 West Africa Ebola virus disease outbreak heavily impacted the Republics of Guinea, Sierra Leone, and Liberia. The outbreak uncovered the weaknesses of the public health systems, including inadequately trained and insufficient health personnel as well as limited and poorly equipped health infrastructures. These weaknesses represent significant threats to global health security. In the wake of the outbreak, affected countries made urgent requests for international engagement to help strengthening the public health systems. Methods: This work describes the successful multi-year implementation of a laboratory capacity building program in the Republic of Guinea. The program integrated biorisk and quality management systems training, infectious diseases diagnostic training, facility engineering and maintenance training, and mentorship to strengthen Guinea's bio-surveillance capacity. Results: The major outcome of these efforts was an established and local staff-operated public health laboratory that performs disease surveillance and reporting and diagnostic of priority diseases and pathogens of security concerns. Conclusions: This work has improved the Guinea country's capabilities to address country public health issues and preparedness to respond to future infectious disease threats.